Regulation of ferroptosis by PI3K/Akt signaling pathway: a promising therapeutic axis in cancer - Su, Hua; Peng, Chao; Liu, Yang (Frontiers in Cell and Developmental Biology, 2024)
The global challenge posed by cancer, marked by rising incidence and mortality rates, underscores the urgency for innovative therapeutic approaches. The PI3K/Akt signaling pathway, frequently amplified in various cancers, is central in regulating essential cellular processes. Its dysregulation, often stemming from genetic mutations, significantly contributes to cancer initiation, progression, and resistance to therapy. Concurrently, ferroptosis, a recently discovered form of regulated cell death characterized by iron-dependent processes and lipid reactive oxygen species buildup, holds implications for diseases, including cancer. Exploring the interplay between the dysregulated PI3K/Akt pathway and ferroptosis unveils potential insights into the molecular mechanisms driving or inhibiting ferroptotic processes in cancer cells. Evidence suggests that inhibiting the PI3K/Akt pathway may sensitize cancer cells to ferroptosis induction, offering a promising strategy to overcome drug resistance. This review aims to provide a comprehensive exploration of this interplay, shedding light on the potential for disrupting the PI3K/Akt pathway to enhance ferroptosis as an alternative route for inducing cell death and improving cancer treatment outcomes.